Spinocerebellar ataxia type 6 protein aggregates cause deficits in motor learning and cerebellar plasticity - Mark, Melanie Danelle; Krause, Martin; Boele, Henk-Jan; Kruse, Wolfgang; Pollok, Stefan; Kuner, Thomas; Dalkara, Deniz; Koekkoek, Sebastiaan; Zeeuw, Chris I. De; Herlitze, Stefan (The journal of neuroscience, 2015)
Spinocerebellar ataxia type 6 (SCA6) is linked to poly-glutamine (polyQ) within the C terminus (CT) of the pore-forming subunits of P/Q-type Ca2+ channels (Cav2.1) and is characterized by CT protein aggregates found in cerebellar Purkinje cells (PCs). One hypothesis regarding SCA6 disease is that a CT fragment of the Cav2.1 channel, which is detected specifically in cytosolic and nuclear fractions in SCA6 patients, is associated with the SCA6 pathogenesis. To test this hypothesis, we expressed P/Q-type channel protein fragments from two different human CT splice variants, as predicted from SCA6 patients, in PCs of mice using viral and transgenic approaches. These splice variants represent a short (CT-short without polyQs) and a long (CT-long with 27 polyQs) CT fragment. Our results show that the different splice variants of the CTs differentially distribute within PCs, i.e., the short CTs reveal predominantly nuclear inclusions, whereas the long CTs prominently reveal both nuclear and cytoplasmic aggregates. Postnatal expression of CTs in PCs in mice reveals that only CT-long causes SCA6-like symptoms, i.e., deficits in eyeblink conditioning (EBC), ataxia, and PC degeneration. The physiological phenotypes associated specifically with the long CT fragment can be explained by an impairment of LTD and LTP at the parallel fiber-to-PC synapse and alteration in spontaneous PC activity. Thus, our results suggest that the polyQ carrying the CT fragment of the P/Q-type channel is sufficient to cause SCA6 pathogenesis in mice and identifies EBC as a new diagnostic strategy to evaluate Ca2+ channel-mediated human diseases.